Influence of Corporate Resource Planning on Business Performance at Nestle Nigeria PLC - Tunmininu Damola Adeleye; Akindeyi Luwoye; Moses Adeleke Adeoye (Universitas Pendidikan Ganesha, 2023)
Enterprise Resource Planning (ERP) systems are an integral element of contemporary business operations, through which organizations monitor their resources, processes and data. Within the framework of Nestle Nigeria Plc, the impact of ERP on business performance is a subject of noteworthy relevance and interest. This research seeks to analyze the influence of corporate resource planning on business performance at Nestle Nigeria PLC. This research uses descriptive research with survey type. The population of this study consists of the ERP software used at Nestle Nigeria Plc. Simple random sampling technique is used in selecting ERP users based on background, position and experience. Questionnaires were used to obtain ERP usage data from respondents. Bivariate regression analysis and Analysis of Variance were used to test the hypothesis at a significance level of 0.05. The findings reveal that the influence of ERP does not have a significant influence on the sales performance of Nestle Nigeria Plc. In addition, ERP has a significant influence on the organizational performance of Nestle Nigeria PLC. That's recommended SMEs, companies, and governments must implement ERP in their businesses to increase sales and organizational performance. Implications of this research can assist Nestle Nigeria management in evaluating the effectiveness of the ERP system that has been implemented, especially in improving operational efficiency, decision making and coordination between departments. The aim of this research is to analyze and evaluate the influence of Enterprise Resource Planning (ERP) on business performance at Nestle Nigeria Plc.